Starch nanocomposite coating containing Thymus fedtschenkoi Ronniger essential oil and thymoquinone: Antibacterial efficacy against two foodborne pathogens inoculated into chicken fillets - Farzaneh Mozafar; Hassan Hassanzadazar; Majid Aminzare; Mahsa Hashemi (Journal of Agriculture and Food Research)
The antipathogenic efficacy of starch/nanoclay biocomposites containing Thymus fedtschenkoi Ronniger essential oil (TFEO) and thymoquinone (TQ) against Listeria monocytogenes and Salmonella enteritidis inoculated in chilled chicken fillets during 12-days of storage was investigated. A dose-response antibacterial effect was observed for all active ingredients (TFEO (0.5 and 1 %) and TQ (0.03 and 0.06 %) individually and in a combination incorporated into starch nanocomposite coating based on well diffusion assay. The inhibitory effect against inoculated L. monocytogenes was better than S. enteritidis for all treatments in chicken fillets. It was more influential at combined concentrations versus both bacteria at an undetected level for L. monocytogenes and a reduction of S. enteritidis by 2.4 log CFU/mL at the end of cold storage. Starch bio-nanocomposites enriched with TFEO and TQ can be proposed as an innovative bioactive packaging material to control the growth of pathogens and increase the microbial safety of meat and meat products.